Physico-chemical Studies and Thermal Decomposition Kinetics of Co(II), Ni(II) and Cu(II) Complexes of Anthracene Carboxaldehyde L-Histidine - Indiradevi, G.; Parameswaran, Geetha; Sabu, P.G. (Asian Journal of Chemistry, 2010)
Cobalt(II), Nickel(II) and Copper(II) complexes of the Schiff base anthracene carboxaldehyde L-histidine were prepared and characterized by elemental analysis, magnetic measurements, conductivity experiments and spectral studies. The thermal decomposition kinetics and mechanism of these chelates was studied from TG data.